Note on “A two-stage adaptive fruit fly optimization algorithm for unrelated parallel machine scheduling problem with additional resource constraints” - Qamhan, Ammar A.; Alharkan, Ibrahim M. (Expert systems with applications, 2019)
In the paper, “A two-stage adaptive fruit fly optimization algorithm for unrelated parallel machine scheduling problem with additional resource constraints” by Xiao-long Zheng and Ling Wang, published in a 2016 volume of Expert Systems With Applications, the authors present a mixed integer linear programming model (MILP) as a solution. This model is stated incorrectly, as it solves the problem of unrelated parallel machine scheduling without the additional resource constraint, which is not the given condition. A counterexample is provided in this note to demonstrate that the solution provided by the given MILP model not feasible for the considered problem. An adjustment on the MILP was developed to find an optimal solution for the problem addressed. The validation of the new MILP is verified.